2005
DOI: 10.1108/14684520510583936
|View full text |Cite
|
Sign up to set email alerts
|

Neural network applications for automatic new topic identification

Abstract: Purpose -This study aims to propose an artificial neural network to identify automatically topic changes in a user session by using the statistical characteristics of queries, such as time intervals and query reformulation patterns. Design/methodology/approach -A sample data log from the Norwegian search engine FAST (currently owned by Overture) is selected to train the neural network and then the neural network is used to identify topic changes in the data log. Findings -A total of 98.4 percent of topic shift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 30 publications
0
42
0
Order By: Relevance
“…Their approach was replicated on Excite search engine data (Ozmutlu and Cavdur, 2005a). Ozmutlu and Cavdur (2005b) and Ozmutlu, et al (2004a) proposed an artificial neural network to automatically identify topic changes, and showed that neural networks successfully provided new topic identification. Application of neural networks for automatic new topic identification does not contain semantic analysis, and relies on the statistical characteristics of the queries.…”
Section: Introduction and Related Researchmentioning
confidence: 99%
“…Their approach was replicated on Excite search engine data (Ozmutlu and Cavdur, 2005a). Ozmutlu and Cavdur (2005b) and Ozmutlu, et al (2004a) proposed an artificial neural network to automatically identify topic changes, and showed that neural networks successfully provided new topic identification. Application of neural networks for automatic new topic identification does not contain semantic analysis, and relies on the statistical characteristics of the queries.…”
Section: Introduction and Related Researchmentioning
confidence: 99%
“…A similar approach based on query content is reported in [9]. Here shifts between sessions are detected with the help of neural networks, also based on time stamp differences and search patterns.…”
Section: Related Workmentioning
confidence: 99%
“…Multiple attributes session segmentation method. Documents [3,4,5,6] were written by same group of authors and gave the same definition for session. These papers adopt the same method to deal with query log and define that all the interactive information between the user and his search engine is a session.…”
Section: Introductionmentioning
confidence: 99%
“…We intend to group these activities together and refer them as a session. Previous documents [1,2,3,4,5,6,7,8] all utilize attribute time interval (TI) to achieve session segmentation. Other attributes like query likelihood (QL) and anchor likelihood (AL) are also used to divide session.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation